LEARNING THE CRITICAL POINTS FOR ADDITION IN MATEMATIKA GASING - Siregar, Johannes Hamonangan; Wiyanti, Wiwik; Wakhyuningsih, Nur Safitri; Godjali, Ali (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2014)
We propose learning Matematika GASING to help students better understand the additionÃ‚Â material. Matematika GASING is a way of learning mathematics in an easy, fun and enjoyableÃ‚Â fashion. GASING is short for GAmpang, aSyIk, and menyenaNGkan (Bahasa Indonesia forÃ‚Â easy, fun and enjoyable). It was originally developed by Prof. Yohanes Surya at the SuryaÃ‚Â Institute in Indonesia to improve the mathematics education in Indonesia. In MatematikaÃ‚Â GASING, there is a step called Ã¢â‚¬Å“the critical pointÃ¢â‚¬Â that needs to be mastered for eachÃ‚Â topic. The focus of our research is the critical point for addition, that is addition of twoÃ‚Â numbers between 1 Ã¢Ë†â€™ 10 with a sum less than 20. The subject is a matriculation class atÃ‚Â STKIP Surya and the research method used is Classroom Action Research. The statisticsÃ‚Â obtained is described using Qualitative Descriptive Statistics.Keyword: Matematika GASING, Addition, Critical Points, Classroom Action Research.Ã‚Â DOI: http://dx.doi.org/10.22342/jme.5.2.1500.160-169